Experimental and numerical investigation on tsunami run-up flow around coastal buildings. Issue 4 (2nd October 2021) - Ishii, Hidenori; Takabatake, Tomoyuki; Esteban, Miguel; Stolle, Jacob; Shibayama, Tomoya
ABSTRACT: Inland tsunami flows can be greatly affected by the presence of coastal buildings. The present study experimentally and numerically investigated the effects of nine different building layouts on 1) the tsunami inundation process and spatial velocity distribution, 2) the flow depth and velocity at a specific point, and 3) the extent of the area where shielding effects take place. High-speed video footage, PIV analysis, and the time history of flow depth, surface velocity and momentum flux demonstrated significant differences in the tsunami run-up behavior among the different building layouts considered. However, it was also shown that a decrease in the surface velocity of flow always appears in front of and immediately behind the building(s), regardless of their layouts. The OpenFOAM simulations performed revealed that significant shielding effects appear in the leeside of the building. These findings can be used when considering where to place evacuation buildings, as constructing them directly behind another study structure could reduce construction costs and increase their stability. The obtained results were also applied to partially validate the method for calculating the channeling effects of tsunami loads provided in ASCE 7–16.